A statistical analysis on IndoPhil Textile Incorporated - Manuel, Jelle Jasmin M.; Pendel, Vivien I.; Vargas, Vina Vivien G. (Diliman, Quezon City College of Engineering, 2001)
The Indophil Textile Incorporated produces yarns for textile manufacture. Several blends are produced and out of these blends, the group concentrated on the analysis of the production of polyester-rayon blend, which is by far the most in demand of the company's products. The data collected revealed different defects observed in yarns such as low tensile strength, unevenness, and presence of neps, thin places, thick places and hairiness. However, analysis was concentrated on the problem of unevenness. The selection came about from the analysis of the data of rejects in production. Out of the 660 tons produced per month, 100 kgs are rejected and the basis for the rejection is unevenness as attested by the production manager. This yarn property is essential in meeting the quality standard of the company. Different machines were tested as to their effects on the different properties/defects observed. Analysis of variance conducted for these different properties revealed that the machines have significant effects on the unevenness and hairiness of the yarns. The Duncan Multiple Range Test showed that significant difference between pairs of means of the properties number of neps and hairiness exist. The individual drums of winding machine were also found out to have no significant effect on the five properties. Denier and machine were also found out to have no effect on the number of neps in the yarn.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics